2017
DOI: 10.1088/2058-9565/aa9861
|View full text |Cite
|
Sign up to set email alerts
|

The cosmic axion spin precession experiment (CASPEr): a dark-matter search with nuclear magnetic resonance

Abstract: The Cosmic Axion Spin Precession Experiment (CASPEr) is a nuclear magnetic resonance experiment (NMR) seeking to detect axion and axion-like particles which could make up the dark matter present in the universe. We review the predicted couplings of axions and axion-like particles with baryonic matter that enable their detection via NMR. We then describe two measurement schemes being implemented in CASPEr. The first method, presented in the original CASPEr proposal, consists of a resonant search via continuousw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 51 publications
0
88
0
Order By: Relevance
“…Applications of such systems range from quantum information processing [1][2][3] and coherent conversion of microwave to optical frequency light [4,5], to microwave components in the form of filters, circulators, isolators and oscillators. Additionally, such systems are used in the study of hybrid quantum systems [6,7], Quantum electrodynamics (QED) [8][9][10], and direct detection of dark matter [11][12][13][14][15]. In the context of dark matter detection, it has been shown that strongly coupled cavity-magnon systems are useful for expanding the range of detectable dark matter masses [11].…”
Section: Introductionmentioning
confidence: 99%
“…Applications of such systems range from quantum information processing [1][2][3] and coherent conversion of microwave to optical frequency light [4,5], to microwave components in the form of filters, circulators, isolators and oscillators. Additionally, such systems are used in the study of hybrid quantum systems [6,7], Quantum electrodynamics (QED) [8][9][10], and direct detection of dark matter [11][12][13][14][15]. In the context of dark matter detection, it has been shown that strongly coupled cavity-magnon systems are useful for expanding the range of detectable dark matter masses [11].…”
Section: Introductionmentioning
confidence: 99%
“…When a spin-1/2 neutron, N , is in the presence of a coherent ALP field, a, assuming both are non-relativistic, the Hamiltonian of their interaction is given by [32,51]…”
Section: Measuring Alps With the Comagnetometermentioning
confidence: 99%
“…Experiments that search for ALPs utilize their coupling to photons [28][29][30][31], gluons [32], electrons [33][34][35][36][37][38], and protons or neutrons [39,40]. In this paper we focus on ALP couplings to electrons and neutrons, re-analyzing decade-old published data from Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Following Ref. [112], the modes are binned into bins of sizes {1, 2, 5, 30} for in the range { [2,4], [5,10], [11,30], [31,4000]}, respectively. The value plotted is the weighted average of C with cosmic variance error at the weighted average with weight proportional to ( + 1), as in the Planck Collaboration pipeline [115].…”
Section: B Cmb Anisotropiesmentioning
confidence: 99%
“…* dgrin@haverford.edu Direct detection experiments [22], indirect detection efforts [23,24], and Large-Hadron Collider (LHC) searches for evidence of supersymmetry [25] have all yielded increasingly stringent upper limits to WIMP properties [26]. The ample unexplored parameter space of QCD axion masses and couplings thus merits exploration, which is underway thanks to experimental efforts like ADMX [27], IAXO [28], MADMAX [29], CASPer [30], and others [20], as well as astrophysical tests using stellar cooling and other effects [31,32]. Most of these efforts probe values m ax 10 −14 eV.…”
Section: Introductionmentioning
confidence: 99%